EFFECTS OF ORAL CLEAR KEFIR PROBIOTICS ON GLYCEMIC STATUS, LIPID PEROXIDATION, ANTIOXIDATIVE PROPERTIES OF STREPTOZOTOCIN INDUCED HYPERGLYCEMIA WISTAR RATS - ., Judiono; ., Djokomoeljanto; S, Hadisaputro (GIZI INDONESIA, 2011)
Hyperglycemia causes excessive free radicals, may increase reactive oxygen species, lipid peroxidation, and reduced antioxidants as well as dysfuntion of the pancreatic β cells. This study was aiming to investigate the effect of oral Clear kefir probiotic on glycemic status, lipid peroxidation and antioxidantive properties of Streptozotocin induced hyperglycemia Wistar Rats. The randomized pretest - posttest control group study design was conducted in 84 malehyperglycemia Wistar rats induced by 40 mg / kg bw streptozotocin (STZ) dissolved in 0,1 M buffer citrate pH 4,5. Rats were randomized into four groups, namely: (1) STZ-induced animals group and given insulin treatment UI/200 0.76 g bw, (2) STZ-induced animals group and given treatment clear kefir 3.6 cc/200 g bw/day for 30 days, (3) STZ-induced animalsgroup as a positive control (ad libitum), (4) normal animals group as a negative control (ad libitum).Blood glucose was measured by enzymatic method. Lipid peroxidation measured of MDA-TBARs by spectrophotometry. SOD and GPX Antioxidants were measured by ELISA. Catalase was measured by spectrophotometry. Probiotics Clear kefir characterization was done by microbiology identification. Data were analyzed by One Way Anova, Kruskall Walis, Duncan, Mann Whitneytest with significance level p 0.05. The result showed that clear kefir supplementation 3.6 cc / day for 30 days administration, affected on blood glucose, MDA and increased antioxidant capacity. Statistical analysis showed that there were respectively decreased of glucose (p0.001), MDA (p0.001). SOD antioxidant capacity was increased (0,05), in addition GPx and Cat were also inceased(p0,001), except in control groups. Probiotics kefir was found as many as 10(6)-10(9) cfu / mL and declined to 10(5) as the decrease in pH during storage, four species of probiotics were detected, such as: Lactobacillus Sp, Sp Lactococcus and Acetobacter and Saccharomyces Sp.In conclusion, kefir supplementation significantlydecreased the blood glucose level, level of MDA and increased of antioxidants capacity. The number of probiotics declined during storage.It is interesting to identify a potential clear kefir probiotics in a pathogenesis of the β cells pancreatic repair and stability product during storage for future study. Keywords: probiotic, hyperglycemia, free radicals, lipid peroxidation, antioxidant